A longitudinal approach to understanding boredom during pandemics: The predictive roles of trauma and emotion dysregulation - Bambrah, Veerpal; Wyman, Amanda; Eastwood, John D. (Frontiers in Psychology, 2023)
Research during the COVID-19 pandemic and prior outbreaks suggest that boredom is linked to poor compliance with critical lifesaving social distancing and quarantine guidelines, as well as to numerous mental health difficulties. As such, continued understanding on what contributes to boredom is imperative. Extending beyond the roles of constraint, monotony, and trait dispositions (e.g., individual differences in boredom propensity), and informed by prior theories on the emotional contributors of boredom, the current longitudinal study examined the predictive role of “pandemic trauma” on people’s boredom, with a focus on how emotion dysregulation mediates this relationship. Community participants (N=345) completed questionnaires three times across an average of three-and-a-half weeks, rating their pandemic trauma, emotion dysregulation, and boredom over the past week each time. Pandemic trauma was assessed with items querying exposure to coronavirus, as well as the financial, resource, and interpersonal pandemic stressors that participants experienced. Emotion dysregulation was assessed with the Difficulties in Emotion Regulation Scale. Boredom was assessed with the short-form Multidimensional State Boredom Scale. The results of a theory-informed mediation model showed that participants’ pandemic trauma at Time 1 positively and modestly predicted their boredom at Time 3 and that this relationship was partially and moderately mediated by participants’ lack of emotional clarity and difficulties with engaging in goal-directed behaviors at Time 2. When people experience pandemic-related trauma, they subsequently struggle to understand their feelings and engage in goal-oriented actions, and, in turn, feel more bored. Theoretical and clinical implications as related to the emotional underpinnings of boredom are discussed.